Shakespeare's Legal Ecologies Law and Distributed Selfhood - Curran, Kevin (Northwestern University Press, 2017)
Shakespeare's Legal Ecologies offers the first sustained examination of the relationship between law and selfhood in Shakespeare's work. Curran argues that law provided Shakespeare with the conceptual resources to imagine selfhood in social and distributed terms, as a product of interpersonal exchange or gathering of various material forces. Curran reveals Shakespeare's distinctly communitarian vision of personal and political experience, the way he regarded living and acting in the world as materially and socially embedded practices. At the center of the book is Shakespeare's fascination with questions fundamental to law and philosophy: What are the sources of agency? For whom am I responsible, and how far does responsibility extend? Curran guides readers through Shakespeare's responses, paying attention to historical and intellectual contexts. The result is a new theory of Shakespeare's relationship to law and an original account of law's role in the ethical work of his writings.